1996
DOI: 10.1113/jphysiol.1996.sp021778
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and pH dependence of skeletal muscle chloride channel ClC‐1.

Abstract: 1. The influence of Cl‐ concentration and pH on gating of the skeletal muscle Cl‐ channel, ClC‐1, has been assessed using the voltage‐clamp technique and the Sf‐9 insect cell and Xenopus oocyte expression systems. 2. Hyperpolarization induces deactivating inward currents comprising a steady‐state component and two exponentially decaying components, of which the faster is weakly voltage dependent and the slower strongly voltage dependent. 3. Open probability (Po) and kinetics depend on external but not internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
200
4

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(232 citation statements)
references
References 27 publications
28
200
4
Order By: Relevance
“…A low pH e diminished the deactivating inward currents without change in time constants, whereas the steady-state component is enhanced (25). However, a low intracellular pH slowed the deactivating current kinetics (25). Moreover, ClC-1 current was activated by hyperpolarization.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A low pH e diminished the deactivating inward currents without change in time constants, whereas the steady-state component is enhanced (25). However, a low intracellular pH slowed the deactivating current kinetics (25). Moreover, ClC-1 current was activated by hyperpolarization.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, ClC-1 current was activated by hyperpolarization. The authors concluded that gating may be controlled by a Cl Ϫ -binding site accessible only from the exterior and possibly by modification of this site by external protonation (25). ClC-2 activity has been shown to be dependent on acidic pH e (26,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the pK a and Hill coefficient of such titration curves, we hoped to infer the most likely sort and number of residues participating in the block. Changes of pH alone have profound effects on the gating of hClC-1, whereas outward current amplitudes do not change considerably (20,21). Block of whole-cell currents was tested by applying repetitive pulses to ϩ50 mV (for maximum channel activation), followed by a hyperpolarizing step at Ϫ125 mV to monitor the deactivation time course (Fig.…”
Section: Dependence Of Chloride Current Block By Znmentioning
confidence: 99%
“…Data were collected, filtered at 3 kHz, and analyzed on an IBM-compatible PC using pCLAMP v6.0 software (Axon Instruments). Parameters such as time constants, apparent open probability, and IC 50 were determined as described previously (16,17). …”
mentioning
confidence: 99%